The Incidence of Psychosis Among Parkinson’s Disease Patients and Associated Factors: A Meta-Analysis - Alsharaeh, Tala; Salahat, Ahmed-Jordan; Alhajahjeh, Abdulrahman; Khudirat, Mohammad; Alashoor, Ali; Shuriquie, Leith; Alquabeh, Batool; AlRyalat, Saif Aldeen (Jordan Medical Journal, 2024)
Introduction: Parkinson’s-induced psychosis is rather prevalent, and it has continuously been linked to poor outcomes. Therefore, detecting this presentation early on, can enhance the quality of life of Parkinson’s disease patients and is therefore a clinical and societal necessity. This systematic review and meta-analysis aimed to estimate the pooled incidence of induced psychosis or psychosis associated with neurodegeneration in Parkinson’s disease. Materials and Methods: PubMed, Scopus, and Cochrane Library were searched to identify studies reporting the prevalence of psychosis in Parkinson’s disease patients. A random-effect meta-analysis was used to pool data from the included studies. The objectives, inclusion criteria, and methods of analysis for this review were specified in advance and documented in a priori protocol (PROSPERO reg. num. CRD42022318920). Results: Twenty studies including 5,123 Parkinson’s disease patients which explored the incidence of presenting symptoms of psychosis in Parkinson’s disease patients were included in the final analysis. The meta-analysis showed that the incidence of psychosis among Parkinson’s disease patients was 35%. A subgroup analysis was performed which showed that disease duration could explain the statistical heterogeneity in this meta-analysis. Conclusion: This systematic review and meta-analysis revealed that psychotic disorders are highly prevalent among Parkinson’s disease patients, indicating an urgent need for further studies to help develop better mechanisms of prevention, detection, and treatment of those disorders among Parkinson’s disease patients in an effort to improve their quality of life.